COST ANALYSIS OF CLINICAL PRACTICE NURSING PROFESSION STUDENTS WITH ACTIVITY BASED COSTING (ABC) METHOD IN Dr. SOEWANDHI HOSPITAL SURABAYA EAST JAVA - M Hasinuddin; Nuh Huda; Abdul Wahid (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
Background and objectives. During this time the unit cost of clinical practice in hospitals that practice becomes a vehicle which has not been done calculation costing more Clinical practice based on estimates, propriety and comparison with the cost of clinical practices from other hospitals. The costing is sometimes caused problems. Currently the cost of student practice in teaching hospitals varies between Rp. 300,000 - Rp. 500,000 / person / month. The problem that exists is how the unit cost and how much it costs the right based on unit cost and other considerations that apply to students practice at the Hospital Clinic as a vehicle for clinical practice. The purpose of this study to determine the unit cost and set the cost of professional practice of nurses that will be proposed applicable professional nurses students at Hospital.Method. This research was a descriptive observational study by conducting a case study in the dr. Soewandhi hospital East Java. Calculation of unit cost carried by Activity Based Costing (ABC), costing more to do content analysis after conducting focus group discussions, as well as other considerations.Research result. The results using the ABC method showed that the unit cost to the cost of professional practice nurses in the hospital Dr. Soewandhi Surabaya is Rp. 460,000, - / month / person, while the cost of practice set by the RS Dr. Soewandhi is Rp. 1.200.000, - / month / person. There is a practice of the profession excess costs Rp. 740,000, -. RS Dr. Surabaya Soewandhi practice fees apply without using a standard based on the unit cost accordingly. Some educational institutions felt the cost was very heavy so the impact to the cancellation of the filing of the professional nurses student practice.Conclusions and recommendations. The hospital used a professional students practice nurses should use the standard fees in accordance with needs through precise calculations that the fees charged to students through educational institutions in accordance with the appropriate calculations.Keyword: ABC system - Profession nurses - Fee Practices